Choosing a multiple radio access technology without tradeoffs between fairness and optimality - Al-Shammari, A.A.A. (Problems of Informatization and Management, 2023)
The task of ensuring the end-to-end quality of service of heterogeneous wireless (HW) networks with random multiple access is considered. The processes of the occurrence of conflicts between the fairness and optimality of route selection and resource allocation in HW networks are analyzed. A technique for eliminating conflicts between fairness and optimality of resource distribution has been developed. It is shown that in the rational definition of radio access technology in heterogeneous networks, the functions of each level and, accordingly, the information parameters of the traffic at this level can be attributed to one of two alternative groups: functions that depend on a specific technical implementation of the network or functions focused on working with applications. Accordingly, a global approach to optimal RAT selection is formulated and an approach for RAT selection using a distributed metaheuristic tabu search algorithm based on the peak speed that users can perceive is proposed. A distributed RAT selection system has been developed.